Distribution of Predisposing Factors for Venue Thromboembolism in a Teaching Hospital - Almaramihi, Waad; Alzuhayri, Jumana; Binafif, Aisha; Abulaban, Aseel; Bawazeer, Duaa; Qari , Mohammed (International Journal of Innovative Research in Medical Science, 2022)
Background: Venous thromboembolism (VTE) are includes both Deep Venus thrombosis (DVT) and Pulmonary Embolism (PE). This study aimed to utilize the causes of VTE and show the demographic data of the patients and effectiveness of treatment of anticoagulant in a teaching hospital in Saudi Arabia. Methods: A retrospective cross sectional study was conducted among KAUH hematology department. This study was approved by the Unit of biomedical ethics of medicine at king Abdulaziz university hospital (KAUH). Target sample included children, adolescent, young adults, adults and geriatrics. Both genders, who diagnosed with VTE. To assess the distribution of predisposing factors. Result: A total of 84 patients diagnosed with VTE, the mean age was 52.73 ± 20.29 years. Female patient constituted of total patients 58.3% (49 cases) were male 41.7% (34 cases) majority of cases were cancer related. Other predisposing factors were hematological malignancies followed by cardiovascular diseases, postoperative patients and immobilization. Half of the sample showed improvement 42 (50%), the most frequently used therapeutic anticoagulation drugs in VTE patients were Warfarin, Enoxaparin and UFH, while the frequency rates were 73, 55 and 41, respectively. Conclusions: In summary, female and geriatrics are at significant risk for VTE more than the others. Majority of the study participants were diagnosed with cancer. The main types were colon cancer, breast, liver and lung cancer. The mortality rate was higher for patients with cancer associated DVT, on the other hand, about half of the patients showed an improvement and full recovery.